2006
DOI: 10.1063/1.2182068
|View full text |Cite
|
Sign up to set email alerts
|

Electrical activation and electron spin coherence of ultralow dose antimony implants in silicon

Abstract: We implanted ultra low doses (2×10 11 cm -2 ) of 121 Sb ions into isotopically enriched 28 Si and find high degrees of electrical activation and low levels of dopant diffusion after rapid thermal annealing. Pulsed Electron Spin Resonance shows that spin echo decay is sensitive to the dopant depths, and the interface quality. At 5.2 K, a spin decoherence time, T 2 , of 0.3 ms is found for profiles peaking 50 nm below a Si/SiO 2 interface, increasing to 0.75 ms when the surface is passivated with hydrogen. Thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
88
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 21 publications
3
88
0
Order By: Relevance
“…Electron spin relaxation times of implanted donors, T 1e , at 5 K are ~15 ms [2], and nuclear spin relaxation times, T 1n are at least 300 times longer [15]. But T 1e and T 1n during EDMR measurements are not yet known.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Electron spin relaxation times of implanted donors, T 1e , at 5 K are ~15 ms [2], and nuclear spin relaxation times, T 1n are at least 300 times longer [15]. But T 1e and T 1n during EDMR measurements are not yet known.…”
mentioning
confidence: 99%
“…Moreover, electron spin relaxation rates of implanted 121 Sb and the Stark effect due to applied electric fields have been previously studied in detail [2,3]. In the limit of a single-donor doped aFET, an EDMR experiment can yield spectra where information on a single nuclear spin state can be deduced from the presence (and absence) of donor hyperfine-split peaks, provided that the read-out time is faster than the spin-flip time of the nuclear spin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This theoretical explanation opens the way to novel microscopic interpretations of a series of pulse electron spin resonance experiments, where the electron spin may be viewed as a spectrometer of low frequency magnetic noise due to a large number of nuclear spins or other magnetic moments. For example, a recent experiment [37] revealed that magnetic noise from the surface must play a role on spin echo decay of antimony impurities implanted in isotopically purified silicon (with a very low density of 29 Si nuclear spins in the bulk).…”
Section: Conclusion and Outlook For The Futurementioning
confidence: 99%
“…Isotope engineered substrates provide a nuclear spin free host environment, resulting in long electron and nuclear spin coherence times of several seconds [3,4]. Spin properties of donor qubit candidates in silicon have been studied mostly for phosphorous and antimony [3][4][5][6]. Bismuth donors in silicon are unique in exhibiting a relatively large zero field splitting of 7.4 GHz.…”
mentioning
confidence: 99%